Representasi Bahasa dan Budaya Daerah dalam Buku Ajar BIPA Sahabatku Indonesia untuk Pelajar: Regional Language and Cultural Representation in the BIPA Textbook Sahabatku Indonesia for Learners - Winasti Rahma Diani; Liana Shinta Dewi; Nilam Rizki Yazera; Naswa Maulida (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
Sahabatku Indonesia 1–7 for Students are the most accessed teaching materials by users as a reference in learning Bahasa Indonesia as a Foreign Language (BIPA) for beginner and intermediate-level students. These books contain linguistic and cultural materials that can be studied by BIPA learners at the school age equivalent to elementary and junior high school levels. Through these books, the teaching content presented serves as a representation of the Indonesian language and culture for BIPA learners who wish to learn and deepen their knowledge about Indonesia. Therefore, this study aims to identify the representation of regional languages and cultures in Indonesia within the Sahabatku Indonesia 1–7 for Students, published by the Ministry of Education and Culture. This research is important as a form of feedback from BIPA practitioners. The results of the study show that the representation in these books is quite diverse, but the distribution of language and cultural content at each level is inconsistent. Regional language representation is most prevalent in level 4 books, while regional cultural representation is most prevalent in level 1 books.